2018
DOI: 10.1111/1742-6723.13148
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of trauma patients attended by ambulance paramedics in Perth, Western Australia

Abstract: The trauma incidence rate increased over time and the majority of patients had low-acuity injuries. Focusing research, training and resources solely on high-acuity patients will not cater for the needs of the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…33 At present, no specific field triage criteria for the management of older adult trauma patients is in use by SJA-WA paramedics. As we have previously highlighted, the incidence of trauma in metropolitan Perth is the highest in those ≥85 years 34 with older adults comprising 35% of the major trauma patients in our current study. It is therefore important that we develop specific prehospital triage criteria to enable the identification of these higher-risk patients in whom TC transport would be beneficial.…”
Section: Discussionsupporting
confidence: 55%
“…33 At present, no specific field triage criteria for the management of older adult trauma patients is in use by SJA-WA paramedics. As we have previously highlighted, the incidence of trauma in metropolitan Perth is the highest in those ≥85 years 34 with older adults comprising 35% of the major trauma patients in our current study. It is therefore important that we develop specific prehospital triage criteria to enable the identification of these higher-risk patients in whom TC transport would be beneficial.…”
Section: Discussionsupporting
confidence: 55%
“…2 Categories may not sum to the total where the crash characteristic was unknown. 3 Vulnerable road users were either motorcyclists (incl. pillion), cyclists or pedestrians.…”
Section: Discussionmentioning
confidence: 99%
“…No electronic record of assessment, intervention, or clinical case notes;2 Paramedics arrived on-scene but there was no patient present (e.g. patient absconded);3 Use of the ambulance for other than delivering patient care, such as transport of equipment;4 Patient transfer between hospitals; 5 Ambulance dispatched but then received a higher priority job or another crew was closer to the scene;6 Individual calls from the scene and states they no longer require the ambulance; 7 Call for an ambulance is falsely and deliberately made;8 Ambulance is sent but cannot locate the MVC. Crash records n=299,601…”
mentioning
confidence: 99%
“…Of the four tertiary and six secondary hospitals in Perth, five provide data to the WA State Trauma Registry (4). The clinical cohort described in this study was SJWA ambulance-transported patients with WA State Trauma Registry records of major trauma from falls and injury severity score (ISS) greater than 15 (4).…”
Section: Methodsmentioning
confidence: 99%
“…Falls have a higher risk of death than other causes of major trauma (1). A recent study of ambulance-transported patients identified falls as the most common cause of major trauma in metropolitan Perth (4). Our study further examines the falls sub-group (4).…”
Section: Introductionmentioning
confidence: 90%